A produção acadêmica acerca dos desastres tecnológicos da mineração em Mariana e Brumadinho (Minas Gerais) - Alfredo Costa; Rebeka Girardi Knop; Miguel Fernandes Felippe (Confins)
In three years, two tailings dam failures have profoundly changed the vision on mining in Brazil. More than three hundred deaths and one thousand kilometers of destroyed rivers are nowadays study objects of almost all scientific fields. Although, many gaps still exist. To comprehend the actual scenario of the academic production on these technological disasters, we did a systematic review of the literature by analytical procedures that are rigorous, explicit, and reproducible. A set of 326 scientific documents was identified, interpreted, and classified by their socio-academic relevance. The results show a greater participation of Geosciences and Science of Law, but there is little dialogue between publications, which can be seen for the low number of citations in most documents.